Aerodynamic resistance of a biofilter with a packing of pine cones - Mitin, Aleksandr; Nikolajkina, Natalya; Pushnov, Aleksandr (Journal of Environmental Engineering and Landscape Management, 2015)
The results of experiments on practical suitability of a biofilter packing made of natural materials – pinecones are provided. Geometric characteristics of a random packing of pine cones are calculated and compared with other types of packings of artificial and natural materials. Aerodynamic tests of the packing are carried out and obtained data are compared with the data for other packings. Some recommendations on improving the performance characteristics of the packing are suggested.